1966
DOI: 10.1149/1.2423801
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Factors Affecting the Critical Potential for Pitting in 18–8 Stainless Steel

Abstract: The concept of a critical potential below which pitting of 18–8 and other passive alloys does not occur in aqueous Cl− media is affirmed. Increasing Cl− concentration shifts the critical potential to more active values. The potential is shifted to more noble values by presence of other anions, e.g., ClO4− , SO4−− , NO3− , OH− , sufficient concentrations of which act as pitting inhibitors. Lowering of temperature similarly enobles the critical potential. The shift at 0°C exceeds the oxidation‐reduction pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
205
2
1

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 532 publications
(237 citation statements)
references
References 10 publications
17
205
2
1
Order By: Relevance
“…The passive film formed on stainless steel in aqueous is predominantly a Cr(III) rich oxide film, which have been reported by some investigators [21][22][23] , z = 3, M = 152 g·mol -1 and ρ = 5.2 g·cm -3…”
Section: Film Thickness Calculationsupporting
confidence: 65%
“…The passive film formed on stainless steel in aqueous is predominantly a Cr(III) rich oxide film, which have been reported by some investigators [21][22][23] , z = 3, M = 152 g·mol -1 and ρ = 5.2 g·cm -3…”
Section: Film Thickness Calculationsupporting
confidence: 65%
“…Recently, Tang et al [14] reported that a good linear relationship exists between the metastable pitting potential and the pitting potential, which is similar to that observed in the present work. has the effect of suppressing the pitting corrosion of stainless steels [11].…”
Section: Electrochemical Corrosion Testmentioning
confidence: 99%
“…On the other hand, it has long been known that SO4 2-has an inhibitory effect on the pitting corrosion of stainless steels [11]. However, there are still many unknown factors regarding the relationship between the initiation and growth mechanisms of pitting corrosion on stainless steels and these impurity ions.…”
Section: Introductionmentioning
confidence: 99%
“…The first model was initially proposed by Leckie and Uhlig [17,18] and Kolotorkyn [19] and suggests that breakdown involves adsorption of Cl À with simultaneous displacement of O 2À from the passive layer, leading to initiation of film destruction.…”
Section: The Corrosion Processmentioning
confidence: 99%